2001
DOI: 10.1128/jcm.39.11.4149-4151.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Latex Agglutination Test (MRSA-Screen) for Detection of Oxacillin Resistance in Coagulase-Negative Staphylococci

Abstract: The MRSA-Screen (Denka-Seiken, Tokyo, Japan) latex agglutination test was evaluated for its ability to detect PBP 2a from 200 clinical isolates of coagulase-negative staphylococci (CoNS; 84 mecA-positive strains and 116 mecA-negative strains) consisting of 108 Staphylococcus epidermidis, 37 S. saprophyticus, 15 S. haemolyticus, 11 S. hominis, 10 S. capitis, 10 S. warneri, and 3 S. lugdunensis species as well as 6 other species of CoNS. The assay was compared with susceptibility testing with an agar screen plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
36
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 16 publications
12
36
0
Order By: Relevance
“…Moreover, in all isolates with the mecA gene, the presence of its PBP2a product was detected. This finding correlates with the data presented by Louie et al (2001); in their study, all isolates with genetically determined methicillin resistance showed agglutination indicating the presence of PBP2a (84 mecA-positive/84 PBP2a-positive isolates). Likewise, Miller et al (2005) demonstrated 100% agreement between the presence of the mecA gene and the modified protein of low affinity to penicillin.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, in all isolates with the mecA gene, the presence of its PBP2a product was detected. This finding correlates with the data presented by Louie et al (2001); in their study, all isolates with genetically determined methicillin resistance showed agglutination indicating the presence of PBP2a (84 mecA-positive/84 PBP2a-positive isolates). Likewise, Miller et al (2005) demonstrated 100% agreement between the presence of the mecA gene and the modified protein of low affinity to penicillin.…”
Section: Discussionsupporting
confidence: 80%
“…We only found major errors (falseresistance) with the oxacillin disk in 2.5% of the isolates, including S. sciuri, S. saprophyticus and S. cohnii-cohnii. Similar discrepancies between phenotypic and genotypic results have been described for S. saprophyticus, S. cohnii, S. warneri, S. capitis, S. lugdunensis and S. xylosus [32].…”
Section: Discussionmentioning
confidence: 60%
“…Total concordance between the latex agglutination test for PBP2a and mecA gene detection by PCR has been observed in isolates that showed false resistance with oxacillin disk diffusion or dilution. The PBP2a test was performed with and without induction, and identical results were observed with the different methods [32,36]. When we analyzed the false positive results obtained with agar dilution (Table 2), we found that eight isolates gave MICs of 0.5 µg/mL (low level of resistance or borderline resistance).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, several studies reported that this technique is sensitive and can be used as a confirmatory test for the results of disk diffusion (Hussain et al, 1998;Cavassini et al, 1999;Louie et al, 2001). Ferreira et al (2003) found that the screening test with 4 µg/ml oxacillin showed 100% sensitivity and 100% specificity versus 94.2% sensitivity and 100% specificity when a concentration of 6 µg/ml had been used, indicating the former as a screening method for CoNS.…”
Section: Discussionmentioning
confidence: 99%